Lack of floristic identity in campos rupestres—A hyperdiverse mosaic of rocky montane savannas in South America - Neves, Danilo M.; Dexter, Kyle G.; Pennington, R. Toby; Bueno, Marcelo L.; de Miranda, Pedro L.S.; Oliveira-Filho, Ary Teixeira (Flora. Morphologie, Geobotanik, Oekophysiologie, 2018)
•campos rupestres do not represent a single floristic group.•Influence from surrounding cerrados drives compositional differentiation in campos rupestres.•Environmental conditions can predict the differentiation amongst campo rupestre floristic groups.•Conservation units fail to protect important parts of the campo rupestre floristic space.•campos rupestres and their surrounding lowland cerrados merit simultaneous conservation attention. The rocky montane savannas of South America, known as campos rupestres in Brazil, where they largely occur, represent a hyperdiverse habitat housing c.15% of the Brazilian vascular flora in less than 1% of the Brazilian territory. Amongst other factors, the remarkable plant diversity in campos rupestres has been attributed to its occurrence as many isolated patches and to floristic influences from surrounding habitats, including lowland woody savannas (cerrado), Atlantic rain forests, seasonally dry woodlands and Amazonian rain forests. However, no study has assessed the degree to which the putative floristic influence from surrounding habitats drives compositional variation in campos rupestres. Here, we used a dataset on the composition of South American woody plant communities (4,637 community surveys, with 115 representing campos rupestres), combined with environmental data, with the aim of characterising and explaining compositional variation of the campos rupestres woody flora. Our results showed that all campos rupestres, including the sites occurring in Amazonian ironstone formations, are more similar to cerrado woody savannas than to any other South American vegetation formations covered in our dataset. Also, multiple campo rupestre floristic groups may be recognized based on distinct species composition and environmental conditions, primarily related to substrate and climate. We stress the importance of considering this floristic heterogeneity in conservation, management and research planning.